ASSESSMENT TECHNIQUES USED BY A TEACHER IN ASSESSING STUDENTS' LANGUAGE SKILLS - Yolanda, Dea (2017)
This research aimed at investigating the assessment techniques used by a teacher in assessing students' language skills in a junior high school in Bandung. It also aimed to reveal the teacher's reason for implementing the techniques as well as the students' responses of the implementation of the techniques. A qualitative case study was employed as a research design in this study. The data were gained from classroom observation, interview, and written document which were then analyzed using the theory of language assessment suggested by Brown (2010). The results revealed that there were five assessment tasks used by the teacher, namely (1) Dicto-Comp, (2) Picture-Cued Task, (3) Short Answer Task, (4) Guided Question and Answer, and (5) Paragraph Construction Task. The teacher implemented the assessment tasks because the tasks were suitable for students to achieve the learning objectives. Students also gave positive responses toward the implementation of the techniques. Despite having difficulties in some aspects, they perceived the assessment tasks as a means of learning to improve their comprehension.